Strategy to Improve Firm Performance Through Operational Efficiency Commitment to Environmental Friendliness: Evidence From Indonesia - Utomo, Mohamad Nur; Wahyudi, Sugen; Muharam, Harjum; Taolin, Maximus Leonardo (Organizations and Markets in Emerging Economies, 2018)
The objective of this study is to examine the effect of controlling shareholders’ monitoring on firm performance through the implementation of operational efficiency commitment to environmental friendliness. Non-financial firms listed on the Indonesia Stock Exchange and joining the Environmental Performance Assessment Program (PROPER) are determined as the sample. Results indicate that controlling shareholders have a positive impact on operational efficiency commitment to environmental friendliness and also on firm performance. In addition, other key findings indicate that the controlling shareholders can improve firm performance through the implementation of operational efficiency commitment to environmental friendliness. The results of this study support the position of the agency theory, the stakeholder theory, and the legitimacy theory. Operational efficiency commitment to environmental friendliness is then suggested to be a meaningful strategy for the firms to obtain sustainable performance.